By the Side of the Road: alone, unequal and unprotected - Rivera Revelo, Laura Yaneth (2023)
This article evidences through a case study, the legal and sociopolitical challenges that States have to guarantee the human rights of irregular migrants, particularly the human rights of women, adults, adolescents and girls to avoid the reproduction of social inequalities, the feminization of poverty and the widening of gender gaps. The analysis focuses on a globalized context that is still patriarchal and in which female migrants who are in the “regulatory gap” use to be potential victims of different types of gender-based and sexual violence (GBSV). In addition, it demonstrates how prioritizing a punitive treatment of social phenomena such as irregular migration, has as an immediate consequence the social and economic marginalization of the victims of illegal trafficking, a precariousness that particularly pushes women to other risks such as being victims of trafficking of people with fines for sexual exploitation, forced prostitution or labor exploitation. The empirical basis of this article is the result of the systematization of information obtained in different training and legal support projects aimed at the Venezuelan population in an irregular migration situation in the municipality of Ipiales and developed by the Guasimí Corporation.